Improving Reading Comprehension of The Eighth-Grade Students of SMP Negeri 19 Palu Through Folklore - Nur Malinda; Mashuri Mashuri; Moh. Abraham Akbar Eisenring; Andi Patmasari (Journal of General Education and Humanities, 2025)
This study aimed to examine the effectiveness of using folklore in improving the reading comprehension skills of eighth-grade students at SMP Negeri 19 Palu. The research employed a pre-experimental design with a one-group pre-test – post-test model. A total of 23 students were selected through a cluster random sampling technique. The data were collected through a reading comprehension test, administered before and after the treatment. The treatment involved teaching reading comprehension through selected Indonesian folktales, including "The Legend of Malin Kundang," "Cinderella," and "Tadulako Bulili." The data were analysed statistically using descriptive analysis and a paired-sample t-test with SPSS version 24. The findings showed an increase in the students' mean scores from 61.85 on the pre-test to 68.15 on the post-test. The significance value of 0.032 (< 0.05) indicated a statistically significant difference between the pre-test and post-test results. Therefore, it can be concluded that using folklore as a learning medium effectively enhances students' reading comprehension, particularly in understanding narrative texts. Moreover, folklore can serve as an engaging and culturally relevant resource to foster students' motivation and interest in learning the English language.